Upaya Pengembangan Sosial Emosional Anak Dimasa New Normal Melalui Media Boneka Tangan di KB Al-Insan Mandiri Krian Sidoarjo - Titik Yuliati; Umi Masturoh (AT-THUFULY : Jurnal Pendidikan Islam Anak Usia Dini, 2021)
Social aspects in early childhood are very important to be developed from an early age. Children who are socially emotionally intelligent will lead them to have a wide social network and in the future will have good cooperation skills. Therefore, in this New Normal period, the role of parents, teachers, and the surrounding environment is very important to support the development of their child's emotional intelligence. In schools, creative teachers are needed in delivering learning. In the aspect of achieving children's social emotional development which includes children being able to obey school rules, children willing to share with friends, showing enthusiasm in playing games, and being able to control feelings (angry, afraid, happy). There are many ways to develop emotional social in children, including a teacher, parent or people around the child making him a good example for children, public figures. In addition, invite children to play with peers, introduce children to new experiences. One of the best efforts to develop aspects of children's social-emotional development is through the media of hand puppets, with this media it is likely that children are able to interact with peers very well.